Thermodynamic Evaluation and Cold Flow Model Testing of an Indirectly Heated Carbonate Looping Process. Issue 9 (22nd August 2013) - Junk, M.; Reitz, M.; Ströhle, J.; Epple, B.; Epple, Bernd
Abstract Carbon capture with subsequent compression and storage is a promising possibility for the reduction of CO2 emissions from coal‐fired power generation. A very efficient post‐combustion CO2 capture technology is the carbonate looping process. To further increase the process efficiency, a new concept is considered where the heat for calcination is transferred from an external combustor to the calciner by means of heat pipes. Some thermodynamic evaluations for a retrofit of a coal‐fired host plant with the indirectly heated carbonate looping process and cold flow model tests of a 300‐kWth test facility that will be erected in 2013 in Darmstadt are presented.